The Existence of Local Wisdom of Islamic Boarding Schools in the Independent Curriculum in Elementary Schools - Noviyanti, Shobihatul Fitroh; Ulfiandi, Ihsan Zikri (Al-Qalam Institue, 2024)
This study aims to explore how religious values ​​derived from the pesantren tradition are integrated into educational activities in elementary schools, as well as their impact on the formation of students' character. This study is based on the importance of early character formation through education that focuses not only on academic aspects, but also on the development of moral and spiritual values. This study uses a qualitative research method by examining in depth the implementation of religious values. The results of the study show that many elementary schools adopt pesantren values ​​not only through religious subjects, but also through students' social interactions and daily activities. Schools also strengthen moral learning by incorporating religious practices such as praying together and implementing rules of politeness into the Independent Curriculum. Pesantren-based teaching methods such as the halaqah system or small study groups are used to create more personal and in-depth interactions between teachers and students that are effective in instilling moral values. These findings are expected to provide insight for other schools and policy makers in developing educational models that integrate moral and religious values ​​into the elementary education curriculum to form strong student character.